Stepping up Efforts in Preventing Maternal Deaths Due to Post-partum Hemorrhage in Nepal: A Critical Review of National Medical Standards: DOI: https://doi.org/10.46405/ejms.v6i9.522 - Jha , Rajshree (Europasian Journal of Medical Sciences, 2024)
Post partum hemorrhage is the leading cause of maternal death globally, as well as in Nepal according to recent Maternal Mortality study 2022. National Medical Standards serve as a country specific reference document for essential clinical materials and tools, that support patient care and service provision. It has been periodically updated to keep up with the latest international medical evidence, keeping in view of the changing international, regional and national legislative and policy and evidence. While the new edition is user friendly and has included secondary postpartum hemorrhage first time, there are few gaps that exist. This commentary, focus is on the Nepal Medical Standards (NMS) more specifically a review of the NMS pertaining to PPH and point out some of the missing opportunities: during antenatal, intra natal and postpartum period. Ensuring optimal health of pregnant women, prevention of anemia, quality monitoring during labor, primary prevention, along with early recognition and timely management are crucial areas that need special focus. A supplementary standard focused on postpartum hemorrhage with relevant professional organizations could address these missing opportunities towards combating PPH in Nepal.